Progression of oncolytic virus in liver cancer treatment - Hua, Xuesi; Xuan, Siyu; Tang, Yangyang; You, Shilin; Zhao, Shang; Qiu, Ye; Li, Yinqing; Li, Yongqing (Frontiers in Oncology, 2024)
The liver plays a crucrial role in detoxification, metabolism, and nutrient storage. Because liver cancer ranks among the top three leading causes of death globally, there is an urgent need for developing treatment strategies for liver cancer. Although traditional approaches such as radiation, chemotherapy, surgical removal, and transplantation are widely practiced, the number of patients with liver cancer continues to increase rapidly each year. Some novel therapeutics for liver cancer have been studied for many years. In the past decade, oncolytic therapy has emerged, in which viruses selectively infect and destroy cancer cells while sparing normal cells. However, oncolytic virotherapy for liver cancer remains relatively obscure due to the aggressive nature of the disease and the limited effectiveness of treatment. To keep pace with the latest developments in oncolytic tumor therapy for liver cancer, this review summarizes basic science studies and clinical trials conducted within 5 years, focusing on the efficacy and safety profiles of the five most commonly used oncolytic viruses: herpes simplex virus, adenovirus, influenza virus, vaccinia virus, and coxsackievirus.